Protective effect of plasma-assisted PVD deposited coatings on Ti–6Al–4V alloy in NaCl solutions. (25th December 2015) - Oliveira, V.M.C.A.; Vazquez, A.M.; Aguiar, C.; Robin, A.; Barboza, M.J.R.
Abstract: Ti–6Al–4V is a (α + β) two-phase alloy with high corrosion resistance in oxidizing acids and neutral media. However, this alloy does not show corrosion resistance in reducing acids and complexing media. Furthermore, the resistance decreases with increasing temperature. Hard nitride based coatings are almost chemically inert and therefore widely used in many applications that require high corrosion resistance. This study aimed to improve the corrosion resistance of Ti–6Al–4V alloy by plasma-assisted PVD deposited TiN and TiAlN/TiAlCrN coatings. The corrosion behavior of uncoated and coated Ti–6Al–4V alloy was evaluated in 3.5 wt.% NaCl solution at 25, 60 and 80 °C, using open-circuit potential versus time measurements, potentiodynamic polarization and electrochemical impedance spectroscopy. The uncoated and coated alloy showed a passive behavior under all conditions. TiN and TiAlN/TiAlCrN coated alloy showed a superior corrosion resistance evidenced by lower corrosion current densities and higher impedance values compared to the uncoated sample. Increasing temperature decreased the corrosion resistance of the uncoated and coated Ti–6Al–4V alloy. Graphical abstract: Highlights: Coated Ti–6Al–4V corrosion resistance was reported at different temperatures. TiN coated alloy showed the best behavior in the NaCl corrosive solution. TiAlN/TiAlCrN coating suffered spallation at all experimental temperatures. Increasing in temperature decreased the corrosion resistance of the alloy.